Understanding the phosphoric acid catalysed ring opening polymerisation of β-Butyrolactone and other cyclic esters. (October 2017) - Macdonald, Emily K.; Shaver, Michael P.
Graphical abstract: Highlights: Phosphoric acids organocatalysts mediate the ring opening polymerisation of cyclic esters. Dual activating behaviour confirmed for these phosphate catalysts in ROP. Lower rates observed for β-BL than other cyclic esters with higher ring strain. Mechanistic studies identify deactivation product where monomer chelates P centre. Decomposition pathway can be prevented by replacing reactive PO bonds with PC bonds. Abstract: A series of phosphoric acid derivatives have been synthesised and their catalytic activity in the ring opening polymerisation of β-Butyrolactone (β-BL), ɛ-caprolactone and rac -lactide probed. Improved synthetic protocols and characterisation data are provided for a range of catalysts substituted with functional groups altering their electron density and p K a . Lower rates are observed for β-BL polymerisations than other aliphatic cyclic esters. By exploring the reaction kinetics and in situ NMR spectroscopy, we show that the activity decreases due to competitive formation of an off-cycle deactivated species through cleavage of catalyst PO bonds.